Allotopic Expression of a Gene Encoding FLAG Tagged-subunit 8 of Yeast Mitochondrial ATP Synthase - I MADE ARTIKA (HAYATI Journal of Biosciences, 2006)
Subunit 8 of yeast mitochondrial ATP synthase is a polypeptide of 48 amino acids encoded by the mitochondrial ATP8 gene. A nuclear version of subunit 8 gene has been designed to encode FLAG tagged-subunit 8 fused with a mitochondrial signal peptide. The gene has been cloned into a yeast expression vector and then expressed in a yeast strain lacking endogenous subunit 8. Results showed that the gene was successfully expressed and the synthesized FLAG tagged-subunit 8 protein was imported into mitochondria. Following import, the FLAG tagged-subunit 8 protein assembled into functional mitochondrial ATP synthase complex. Furthermore, the subunit 8 protein could be detected using anti-FLAG tag monoclonal antibody. Key words: allotropic expression, ATP synthase, mitochondria, yeast